Compensatory Intracranial Arterial Dilatation in Extracranial Carotid Atherosclerosis: The Northern Manhattan Study. Issue 6 (August 2015) - Gutierrez, Jose; Elkind, Mitchell S. V.; Gomez-Schneider, Maia; DeRosa, Janet T.; Cheung, Ken; Bagci, Ahmet; Alperin, Noam; Sacco, Ralph L.; Wright, Clinton B.; Rundek, Tatjana
Background: There is a scarcity of data supporting the association between atherosclerosis and dolichoectasia in unbiased samples. Aims: To test the hypothesis that the association between dolichoectasia and extracranial carotid atherosclerosis depends on the degree of collateral circulation. Methods: The Northern Manhattan Study magnetic resonance imaging substudy consists of 1290 participants who remained stroke-free at the time of magnetic resonance imaging. Arterial diameters were collected in all participants with available magnetic resonance angiography. Dolichoectasia was defined as a head-size adjusted diameter >2 standard deviation for each artery. Carotid Doppler was used to evaluate for carotid atherosclerosis (carotid plaque, maximum plaque thickness and carotid intima media thickness). Results: We included 994 participants with available Doppler and magnetic resonance angiography data (mean age 63 years, 60% female). Any dolichoectasia was reported in 16% of participants, 54% had at least one carotid plaque and the mean carotid intima media thickness was 0·92 ± 0·09 mm. After adjusting for demographic and clinical characteristics, there was no association between markers of carotid atherosclerosis and dolichoectasia. However, stratifying by collaterals, it was observed that dolichoectasia was more likely in the anterior and posterior circulations when collaterals were available among participants with carotid atherosclerosis. These associations were confirmed by noting an increment in arterial diameters in the corresponding arteries ipsilateral and contralateral to each carotid as well as in the posterior circulation. Conclusions: We did not find an association of extracranial carotid atherosclerosis with dolichoectasia. However, we found that dolichoectasia is more frequent when intracranial collaterals are available suggesting a compensatory process that needs further investigation.